Therapeutic potential and molecular mechanisms of salidroside in ischemic diseases - Han, Jingxuan; Luo, Lailiu; Wang, Yicheng; Wu, Shourong; Kasim, Vivi (Frontiers in Pharmacology, 2022)
Rhodiola is an ancient wild plant that grows in rock areas in high-altitude mountains with a widespread habitat in Asia, Europe, and America. From empirical belief to research studies, Rhodiola has undergone a long history of discovery, and has been used as traditional medicine in many countries and regions for treating high-altitude sickness, anoxia, resisting stress or fatigue, and for promoting longevity. Salidroside, a phenylpropanoid glycoside, is the main active component found in all species of Rhodiola. Salidroside could enhance cell survival and angiogenesis while suppressing oxidative stress and inflammation, and thereby has been considered a potential compound for treating ischemia and ischemic injury. In this article, we highlight the recent advances in salidroside in treating ischemic diseases, such as cerebral ischemia, ischemic heart disease, liver ischemia, ischemic acute kidney injury and lower limb ischemia. Furthermore, we also discuss the pharmacological functions and underlying molecular mechanisms. To our knowledge, this review is the first one that covers the protective effects of salidroside on different ischemia-related disease.